EFFECTIVENESS OF THE POLICY OF THE PUBLIC WORKS AND SPATIAL PLANNING DEPARTMENT (PUPR) OF RIAU PROVINCE IN OVERCOMING CONGESTION IN PEKANBARU CITY 2019-2022 - Diyanti, Audry; ,, Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Pekanbaru City is one of the largest economic centers on the island of Sumatra and is included as a city with a high rate of growth, migration, and urbanization. This growth has led to increasingly severe traffic congestion problems, especially in strategic areas such as the SKA Mall and Jalan Sudirman. Traffic congestion is a major problem faced by large cities, a common problem that occurs with high mobility is the problem of increasingly growing community activities. In an effort to address this problem, the local government has implemented the construction of flyovers as a solution to improve traffic flow. Through the Public Works and Spatial Planning (PUPR) Department of Riau Province, the construction of a flyover to overcome congestion. To determine the effectiveness of the policies that have been issued and using the theory from Riant Nugroho 2018 which consists of 5 indicators: appropriate policy, appropriate implementation, appropriate target, appropriate environment, and appropriate process. The research method for this thesis uses a qualitative descriptive approach. This study aims to provide a comprehensive overview of the effectiveness of the flyover construction policy and its impact on traffic congestion in Pekanbaru City The construction of flyovers in Pekanbaru City has had a positive impact in reducing traffic congestion. However, there are still aspects that need to be improved to achieve optimal effectiveness in infrastructure policies. By improving policy planning, implementation, and evaluation, it is hoped that future infrastructure development will be more effective in addressing congestion and improving the quality of life for residents of Pekanbaru City. This research is expected to serve as a reference for policymakers and future researchers in the fields of transportation and infrastructure development. Keywords : Effectiveness, Policy, Congestion